The internationalization of social work. Emerging discourses from the Erasmus Mundus Advances program. - Di Matteo, Claudia; Ganne, Claire (Social Work Education, 2020)
Nowadays, an increased number of international social work (ISW) educational programs have been developed with the goal to equip practitioners to face the social problems in the new modern era. Within our globalized world, social work is in the quest for professionals with a global mind-set and nontraditional abilities and skills. This article presents the findings of an explorative research carried out during the ISW master program called Advances. The qualitative research aimed to explore the perceptions, believes and opinions of those students and alumni who have been enrolled in the Advances program who were subsequently asked to think critically and reflect about their international experience. The Advances program is a practical example that might be helpful to reflect on both how to develop a collaborative process between international social workers during the early years of education and how to build commonalities and fight for a common cause, improving the global/local social workers' mind-set, sharing cross-national concerns more than look for an international ideological definition of what should be (International) Social Work.